From Scrolling to Studying: Leveraging Digital Social Media Environment for Academic and Non-Academic Achievement at MTS Pembangunan Mandirancan - Humaydiy, Agus Alif; Yasin, Robby Lafadza; Rasyad, Muhammad Ghaffar; Cahyani, Dewi; Ali, Moh (CV. Strata Persada Academia, 2025)
This study investigates the influence of the digital social media environment on academic and non-academic achievement among junior high school students at MTs Pembangunan Mandirancan, Kuningan Regency, Indonesia. Against the backdrop of increasing digital engagement among adolescents, this research addresses a gap in the literature by focusing on students at the MTs level—a group often overlooked in previous studies. Employing a quantitative associative explanatory approach, the study involved 100 students selected through stratified random sampling from a population of 255 active social media users. Data were collected using validated Likert-scale questionnaires and official academic documentation. Descriptive and inferential statistical analyses, including Pearson correlation and multiple linear regression, were conducted using SPSS. The results reveal a moderate and statistically significant positive correlation between the digital social media environment and both academic achievement (r = 0.512, p < 0.01) and non-academic achievement (r = 0.478, p < 0.01). These findings suggest that, when used constructively, social media can support student learning, collaboration, and engagement in extracurricular activities. It is recommended that educators, parents, and policymakers promote digital literacy and responsible media use, integrating social media into learning strategies and school programs to foster critical thinking, creativity, and social competence among students.